H HUBUNGAN FAKTOR INDIVIDU TERHADAP KINERJA KADER JUMANTIK - Annisa Avitami Kesuma Wardhani; Dwi Yulia Marita Sari; Febria Listina; Dian Utama Pratiwi Putri (PT.Mantaya Idea Batara, 2023)
T The less than optimal performance of jumantik cadres will have an impact on the lack of supervision of mosquito nests and increase cases of DHF (Dengue Hemorrhagic Fever) disease (IR). Data for inactive jumantik cadres were 45 people (61.6%) who were active as many as 28 people (38.4%) Data from Tulang Bawang district noted that in 2021 the Menggala Health Center had the most positive cases and suspected dengue fever, there were 54 positive case findings and 1 case dengue death. This study aims to see the correlation of individual factors on the performance of jumantik cadres in the Working Area of the Menggala Health Center in 2022. This research is an analytical research using a cross sectional approach which has a sample size of 65 jumantik cadres with a quota sampling technique using a questionnaire research instrument and filled in by respondents, bivariate analysis using the chi square test. There is a significant relationship between motivation P value = (0.015), OR = (3.714), satisfaction P value = (0.19), OR = (3.470), attitude P value = (0.023), OR = (3.375) with performance jumantik cadres in the Menggala Health Center working area. The Menggala Health Center office provides training for cadres related to management, implementation, monitoring, and mosquito nests, facilitating cadres in the form of office stationery and equipment to facilitate the performance of jumantik cadres at work.